The secretome of stressed peripheral blood mononuclear cells increases tissue survival in a rodent epigastric flap model. Issue 1 (22nd September 2020) - Hacker, Stefan; Mittermayr, Rainer; Traxler, Denise; Keibl, Claudia; Resch, Annika; Salminger, Stefan; Leiss, Harald; Hacker, Philipp; Gabriel, Christian; Golabi, Bahar; Pauzenberger, Reinhard; Slezak, Paul; et al.
Abstract: Reconstructive surgery transfers viable tissue to cover defects and to restore aesthetic and functional properties. Failure rates after free flap surgery range from 3 to 7%. Co‐morbidities such as diabetes mellitus or peripheral vascular disease increase the risk of flap failure up to 4.5‐fold. Experimental therapeutic concepts commonly use a monocausal approach by applying single growth factors. The secretome of γ‐irradiated, stressed peripheral blood mononuclear cells (PBMCsec) resembles the physiological environment necessary for tissue regeneration. Its application led to improved wound healing rates and a two‐fold increase in blood vessel counts in previous animal models. We hypothesized that PBMCsec has beneficial effects on the survival of compromised flap tissue by reducing the necrosis rate and increasing angiogenesis. Surgery was performed on 39 male Sprague–Dawley rats (control, N = 13; fibrin sealant, N = 14; PBMCsec, N = 12). PBMCsec was produced according to good manufacturing practices (GMP) guidelines and 2 ml were administered intraoperatively at a concentration of 2.5 × 10 7 cells/ml using fibrin sealant as carrier substance. Flap perfusion and necrosis (as percentage of the total flap area) were analyzed using Laser Doppler Imaging and digital image planimetry on postoperative days 3 and 7. Immunohistochemical stainings for von Willebrand factor (vWF) and Vascular Endothelial Growth Factor‐receptor‐3 (Flt‐4) were performed on postoperative day 7 to evaluate formation of blood vessels and lymphatic vessels. Seroma formation was quantified using a syringe and flap adhesion and tissue edema were evaluated clinically through a cranial incision by a blinded observer according to previously described criteria on postoperative day 7. We found a significantly reduced tissue necrosis rate (control: 27.8% ± 8.6; fibrin: 22.0% ± 6.2; 20.9% reduction, p = .053 vs. control; PBMCsec: 19.1% ± 7.2; 31.1% reduction, p = .012 vs. control; 12.9% reduction, 0.293 vs. fibrin) together with increased vWF+ vessel counts (control: 70.3 ± 16.3 vessels/4 fields at 200× magnification; fibrin: 67.8 ± 12.1; 3.6% reduction, p = .651, vs. control; PBMCsec: 85.9 ± 20.4; 22.2% increase, p = .045 vs. control; 26.7% increase, p = .010 vs. fibrin) on postoperative day 7 after treatment with PBMCsec. Seroma formation was decreased after treatment with fibrin sealant with or without the addition of PBMCsec. (control: 11.9 ± 9.7 ml; fibrin: 1.7 ± 5.3, 86.0% reduction, 0.004 vs. control; PBMCsec: 0.6 ± 2.0; 94.8% reduction, p = .001 vs. control; 62.8% reduction, p = .523 vs. fibrin). We describe the beneficial effects of a secretome derived from γ‐irradiated PBMCs on tissue survival, angiogenesis, and clinical parameters after flap surgery in a rodent epigastric flap model.